IMPLEMENTASI PARTISIPASI AKTIF GURU DALAM MENINGKATKAN KINERJA GURU DI SDN DERMO I BANGIL - Yuli Wariyanti; Ahmad Thohirin; M. Furqon Wahyudi (Jurnal Manajemen Pendidikan, 2026)
This study aims to explore the implementation of teachers’ active participation in improving teacher performance at SDN Dermo I Bangil by highlighting its meanings, forms, and implications within the context of a primary school organization. The phenomenon of suboptimal teacher performance is often associated with limited opportunities for participation in decision-making processes and professional development at the school level. This study employed a qualitative approach with a case study design, which was selected to obtain an in-depth and contextual understanding of the phenomenon. Data were collected through semi-structured interviews, participant observation, and document analysis involving the principal and teachers selected using purposive sampling, complemented by snowball sampling to enrich the data. The findings reveal three main themes: teachers’ participation in school decision-making, participation in professional development, and participation as a driver of improved teacher performance. The results indicate that meaningful teacher involvement fosters a sense of ownership, professional responsibility, and work motivation, which positively influence teacher performance. However, the study also identifies barriers to participation influenced by organizational culture and differences in teachers’ experiences. Theoretically, this study reinforces the perspectives of participative leadership and distributed leadership in the context of primary education.